Gap bridge track device and comprehensive railway maintenance vehicle set - TANG PENG; ZHANG SHENG; ZHANG JINTING; SHI TIANLIANG; HUANG XINXIA (2024)
The embodiment of the utility model provides a gap bridge track device and a comprehensive railway maintenance vehicle set. The gap bridge track device comprises a first fixed track and a second fixed track which are arranged on a transition track and arranged on the tops of adjacent carriages of a railway train set. One end of the transition rail is movably connected with the first fixed rail, and the other end is connected with the second fixed rail; and in a curve line walking state, the transition track can rotate relative to the first fixed track, and the transition track can move in the longitudinal direction relative to the second fixed track. According to the invention, the vehicle group can smoothly pass through a curve ramp and the like without influencing the running of the vehicle group; by means of the gap bridge rail device, materials, machines and tools and the like in multiple carriages of a train set can be rapidly transferred through crane hoisting, efficiency is high, and safety and reliabi